1980
DOI: 10.1515/zna-1980-1222
|View full text |Cite
|
Sign up to set email alerts
|

1,2,4-Triazole Complexes XIV

Abstract: Heat capacity measurements on Mn(trz)2(NCS)2 in the range 1 -90 K are reported. A ?.-anomaly is found at Tc -3.292(6) K. From a comparison of the high-temperature specific heat to the predictions from series expansions the intralayer exchange constant is found to be J/k = 0.245(5) K. From the total magnetic energy involved in the transition the value J/k = -0.254(8) K is calculated. These results compare favourably with previous data from susceptibility measurements.From very recent X-ray diffraction experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

1983
1983
2000
2000

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…An interesting series of layered complexes of 1,2,4-triazole with divalent metal thiocyanates has recently been investigated by Engelfriet [130][131][132][133][134][135][136][137]. A portion of the structure of these molecules is illustrated in Fig.…”
Section: Canting and Weak Ferromagnetismmentioning
confidence: 99%
“…An interesting series of layered complexes of 1,2,4-triazole with divalent metal thiocyanates has recently been investigated by Engelfriet [130][131][132][133][134][135][136][137]. A portion of the structure of these molecules is illustrated in Fig.…”
Section: Canting and Weak Ferromagnetismmentioning
confidence: 99%
“…Soon after Haasnoot et al found thermochroism above room temperature in an iron(II) compound with the ligand 1 H -1,2,4-triazole (Htrz), several research groups started to investigate iron(II) compounds with (substituted)-1,2,4-triazoles ((R-)trz). Of special interest are the 4-R-1,2,4-triazoles, for these are known to give polynuclear linear products with a triple bridge. ,, The length of these products varies from dinuclear compounds with one triple bridge, via trinuclear compounds, , to polynuclear, linear-chain products. ,,,, A two-dimensional compound with 4,4‘-bis(1,2,4-triazole) was also obtained. , A large number of these compounds show ST behavior with a variety of transition temperatures (80 K < T 1/2 < 420 K) and transition curve shapes.…”
Section: Introductionmentioning
confidence: 99%
“…Soon after Haasnoot et al 11 found thermochroism above room temperature in an iron(II) compound with the ligand 1H-1,2,4triazole (Htrz), several research groups started to investigate iron(II) compounds with (substituted)-1,2,4-triazoles ((R-)trz). [12][13][14][15][16][17][18][19][20][21] Of special interest are the 4-R-1,2,4-triazoles, for these are known to give polynuclear linear products with a triple bridge. 13,16,18 The length of these products varies from dinuclear compounds with one triple bridge, 22 pounds, 13,18 to polynuclear, linear-chain products.…”
Section: Introductionmentioning
confidence: 99%
“…This difference is significantly larger than for coordination compounds with unsubstituted 1,2,4-triazole (Engelfriet, Groeneveld & Nap, 1980, and references cited therein). This indicates a more defined localization of the double-bond character between N1--C5 and N2-C3.…”
mentioning
confidence: 82%
“…In order to be able to study magnetic interactions between first-row transition-metal ions, magnetochemists need ligands which can create a [Mn(C4H4N6)2(H20)2] (NO3)2.2H20 pathway for the magnetic exchange between metal ions. During the last decade one of the ligands used for this purpose is 1,2,4-triazole (Engelfriet, Groeneveld & Nap, 1980, and references cited therein). 4-Alkylsubstituted triazoles have been studied extensively (Vos, Haasnoot, Verschoor, Reedijk & Schaminee, 1985, and references cited therein).…”
mentioning
confidence: 99%